To expand the expression \((3x^2 - 2x - 2)(3x^2 + 2x + 4)\) and collect like terms, we can use the distributive property (also known as the FOIL method for binomials). Here's how we can break it down step by step:
-
Expand Each Term:
- Distribute each term in the first polynomial \((3x^2 - 2x - 2)\) to each term in the second polynomial \((3x^2 + 2x + 4)\).
First, multiply \(3x^2\) by each term:
- \(3x^2 \cdot 3x^2 = 9x^4\)
- \(3x^2 \cdot 2x = 6x^3\)
- \(3x^2 \cdot 4 = 12x^2\)
Next, multiply \(-2x\) by each term:
- \(-2x \cdot 3x^2 = -6x^3\)
- \(-2x \cdot 2x = -4x^2\)
- \(-2x \cdot 4 = -8x\)
Finally, multiply \(-2\) by each term:
- \(-2 \cdot 3x^2 = -6x^2\)
- \(-2 \cdot 2x = -4x\)
- \(-2 \cdot 4 = -8\)
-
Combine all the terms together: \[ 9x^4 + 6x^3 + 12x^2 - 6x^3 - 4x^2 - 8x - 6x^2 - 4x - 8 \]
-
Combine like terms:
- \(9x^4\) (only one term of \(x^4\))
- \(6x^3 - 6x^3 = 0\) (the \(x^3\) terms cancel out)
- \(12x^2 - 4x^2 - 6x^2 = 2x^2\)
- \(-8x - 4x = -12x\)
- \(-8\) (only one constant term)
Final result: \[ 9x^4 + 2x^2 - 12x - 8 \]
Thus, the expression in standard form is: \[ 9x^4 + 2x^2 - 12x - 8 \]